An Aerodynamic Study of a Domestic Scale Horizontal Axis Wind Turbine With Varied Tip Configurations. (2015) - Ali, Abdulkadir; Chowdhury, Harun; Loganathan, Bavin; Alam, Firoz
Abstract: This paper primarily aims to investigate the aerodynamic characteristics of a small Horizontal Axis Wind Turbines (HAWT) with different blade tip configurations to enhance power generation efficiency. To understand the flow behavior at the tip and to reduce the induced drag due to tip vortex, three different blade configurations (upwind winglet, downwind winglet and blade without a winglet) were designed, manufactured and tested under a range of wind speeds and yaw angles. The results show that the winglet has significant effect on the aerodynamic performance of the wind turbine blade used for domestic scale wind generator. The results indicated an increase of lift-to-drag ratio with the upwind winglet by around 26% compared to a straight blade with no winglet whereas the downwind winglet results in a decrease of lift-to-drag ratio about 27%.